234k views
0 votes
15. 3(3 + 2) + 2(x + 1) =
-5(x – 3)

1 Answer

2 votes

Answer:

x = -2/7

Explanation:

3(3 + 2) + 2(x + 1) = -5(x – 3)

Combine like terms

3(3 + 2) + 2(x + 1) = -5(x – 3)

3(5) + 2(x + 1) = -5(x – 3)

15 + 2(x + 1) = -5(x – 3)

Distribute

15 +2x+2 = -5x +15

Combine like terms

2x+17 = -5x+15

Add 5x to each side

2x+5x +17 = -5x+5x +15

7x +17 = 15

Subtract 17 from each side

7x+17-17 = 15-17

7x = -2

Divide each side by 7

7x/7 = -2/7

x = -2/7

User USeemSurprised
by
5.7k points